2016
DOI: 10.3389/fpsyg.2016.00631
|View full text |Cite
|
Sign up to set email alerts
|

Animal Assisted Therapy (AAT) Program As a Useful Adjunct to Conventional Psychosocial Rehabilitation for Patients with Schizophrenia: Results of a Small-scale Randomized Controlled Trial

Abstract: Currently, one of the main objectives of human–animal interaction research is to demonstrate the benefits of animal assisted therapy (AAT) for specific profiles of patients or participants. The aim of this study is to assess the effect of an AAT program as an adjunct to a conventional 6–month psychosocial rehabilitation program for people with schizophrenia. Our hypothesis is that the inclusion of AAT into psychosocial rehabilitation would contribute positively to the impact of the overall program on symptomol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
93
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(97 citation statements)
references
References 61 publications
3
93
1
Order By: Relevance
“…In the study by Calvo et al [47] of adult inpatients with schizophrenia, DAT was assessed as an adjunct to, and in comparison with, conventional psychosocial rehabilitation.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Calvo et al [47] of adult inpatients with schizophrenia, DAT was assessed as an adjunct to, and in comparison with, conventional psychosocial rehabilitation.…”
Section: Resultsmentioning
confidence: 99%
“…Adults participating in a trauma treatment analogue experienced significant reductions in distress and depressive symptoms [34]. Adult inpatients diagnosed with schizophrenia had reduced anhedonia [35] and other negative symptoms [36]. Adults hospitalised for substance dependence demonstrated increased therapeutic alliance [37] and interpersonal socialisation [38].…”
Section: Introductionmentioning
confidence: 99%
“…A number of these studies reported that the presence of canines had a direct impact on the primary diagnoses and clinical symptomatology of the participants [3136]. These were factors that were specifically targeted by the intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence in favor of the wellbeing benefits associated with interacting with a pet (typically a dog), has led to a rise in the use of animal-assisted interventions (AAI) in structured visitation programs to organizations (1), such as nursing homes (10, 11), healthcare settings (1214), and educational institutions (1517). Historically, dogs in the workplace has typically been limited to allowing trained assistance dogs public access in office-based buildings, to support their owners who may have visual or hearing difficulties (18, 19), or other medical problems such as diabetes.…”
Section: Introductionmentioning
confidence: 99%